Tracing the career trajectories of female academics at two Universities - Raymond, Zaakira Nikaath (My University, 2016)
This research traced the career trajectories from a cohort of female academics that were recipients of the Carnegie grant. These female academics were from two primary universities; the University of the Witwatersrand (Wits) and the University of Cape Town (UCT). The primary aim of the research was to explore the career trajectories of this cohort of female academics and gain further insight into the enablers and barriers to productivity and at their university. The impact of these enablers and challenges on the retention and attrition patterns was then analysed. The critical factors that were explored when interpreting retention and attrition were gender, race, intersectionality, belonging and culture. This analysis was enabled by applying critical race theory, intersectionality, and theories of belonging and non-belonging to the data. Due to the nature of this research, a qualitative approach was taken with the use of semi-structured interviews. The sample consisted of twenty-two female academics. In depth interviews were audio-recorded and transcribed and analysed using critical discourse analysis as well as thematic analysis proposed by Braun and Clarke (2006). The results indicated that female academics face a great deal of challenges within the higher education sector. These challenges often present as obstacles in their career progression. More importantly, black female academics face greater barriers because of the intersectional nature of their identity as being both black and female, amongst other identity categories. One of the leading causes to these barriers is based on the underlining institutional culture that exists at each university that is instilled through various systems and structures. One of the key enablers for this cohort of women academics was the Carnegie grant that they had received. For many, it provided scarce financial resources to focus on conducting quality research and dislodged the systems of patriarchal patronage which sometimes leaves women’s development at the mercy of male colleagues. The research suggests that notions of belonging are tied to epistemic access and the recognition and affirmation of the multiple identities that constitute women.
A research project submitted in partial fulfilment of the requirements for the degree of Masters by Coursework and Research Report in the field of Industrial/Organisational Psychology. Faculty of Humanities, University of the Witwatersrand, Johannesburg 6 June 2016
Keywords: Women - Education; Sex discrimination in education.; Women's studies.; Feminism